Familial Hyperinsulinism due to HNF4A Deficiency and Benign Premature Adrenarche: A Case Report - Edward Compton; David H. Geller; Alaina Vidmar (University Library System, University of Pittsburgh, 2021)
Background: Familial Hyperinsulinism due to HNF4A deficiency (FHI-HNF4A) is a form of diazoxide-sensitive, diffuse hyperinsulinism, characterized by transient or persistent hyperinsulinemic hypoglycemia, and a propensity to develop Maturity-Onset Diabetes of the Young type 1 (MODY1). The association between FHI-HNF4A deficiency and benign premature adrenarche (BPA) is unknown. The Case: We report the case of a 5-year-old girl with FHI-HNF4A, controlled on diazoxide, who presented with BPA and Tanner stage III pubic hair associated with body odor and acne. Work-up revealed elevated dehydroepiandrosterone sulfate (DHEAS), elevated free testosterone, and advanced bone age. Insulin levels were elevated in the setting of normal fasting blood glucose. We discuss the possible hormonal underpinnings of hyperandrogenism. Conclusion: Though the underlying pathophysiology of this phenotype is unclear, a possible synergistic mechanism exists between insulin-induced hyperandrogenism and HNF4A deficiency leading to a transient decrease of SHBG and thus increased free testosterone levels. Further investigation is required to determine the association between HNF4A dysfunction and BPA.